A Meta-Analysis of the Relationship Between Chief Executive Officer Tenure and Firm Financial Performance: The Moderating Effects of Chief Executive Officer Pay and Board Monitoring. Issue 3 (June 2021) - Cao, Xian; Im, Junyon; Syed, Imran
Prior empirical research investigating the relationship between chief executive officer (CEO) tenure and firms' financial performance has shown inconclusive results. Based on arguments of agency and behavioral agency theories, we suggest that this relationship is nuanced and may vary depending on CEO pay and board monitoring. In response to these arguments, we meta-analytically test 385 studies ( n = 1, 029, 602). We find that CEO tenure is positively related to firms' financial performance. This positive relationship is enhanced when CEOs receive higher cash compensation or hold more stock ownership. On the other hand, the above positive relationship becomes weaker when CEOs receive higher long-term incentives or when the firm has more independent board directors. These findings suggest that CEO pay and board monitoring, or agency mechanisms in general, can offer new research avenues to help explore boundary conditions of the CEO tenure and firms' financial performance relationship.